Medidas estruturais para a racionalização da judicialização da saúde: experiências práticas e proposta de reunião de demandas para julgamento - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This dissertation addresses the issue of the judicialization of health in Brazil, with the aim of identifying this phenomenon as a structural problem. This work seeks to present a proposal for the application of structural measurements to rationalize judicial intervention in public health policy, through the gathering of demands that deal with similar requests, with the unified practice of evidentiary acts and a single judgment in a single court. The relevance of the topic can be seen in the proposal to overcome an individualized vision of judicialization, which leads to budgetary distortions and violations of equality and legal security, to promote global solutions of interest to the entire society. For discussion, the deductive method was used and, within a translational bias, semi-structured interviews were carried out with state attorneys working on health demands. It was observed, from a practical perspective, that the gathering of demands that request the same treatment for the same disease is based on procedural legislation that provides for the carrying out of cooperative acts between judges and has the potential to promote the construction of multi-handed solutions for judicialization of health under a collective bias and rational intervention in established public policy.
Keywords: Judicialização da saúde; políticas públicas de saúde; processos estruturais; Sistema Único de Saúde; cooperação judiciária; Judicialization of health; public policies; structural lawsuits; Unified Health System; judicial cooperation; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO